Revisiting Ahmad Amin’s Literary Criticism in the Age of Artificial Intelligence: Bridging Evaluative Tradition and Interpretive Approaches - Maula, Ismatul; Tatik Mariyatut Tasnimah (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
This study revisits Ahmad Amin’s concept of literary criticism through his seminal work Al-Naqd al-Adabī and examines its relevance in the age of Artificial Intelligence. Employing library research with an intellectual history approach and qualitative content analysis, the study reconstructs Ahmad Amin’s critical framework and situates it within the development of modern Arabic literary criticism. The findings reveal that Ahmad Amin conceptualizes literary criticism as an intellectual activity that integrates interpretation and evaluation rather than privileging one over the other. He argues that critical judgment should emerge from a thorough understanding of literary texts and be guided by objectivity, aesthetic sensitivity (dhawq), broad knowledge, and intellectual integrity. The study further demonstrates that Ahmad Amin occupies a transitional position between the evaluative tradition of classical Arabic criticism and the interpretive approaches of modern literary criticism. In contemporary contexts, his ideas offer a valuable framework for understanding the role of human judgment in AI-assisted literary criticism. While artificial intelligence can support textual interpretation and analysis, aesthetic evaluation and intellectual responsibility remain fundamentally human domains. These findings highlight the continuing relevance of Ahmad Amin’s literary-critical thought for contemporary literary studies.